Corporate Social Responsibility Proposals and Firm Valuation - Pyung Kun Chu (International Journal of Financial Studies, 2021)
Corporate social responsibility (CSR) is a topic which has recently been attracting an increasing amount of attention with respect to corporate operations, and shareholder proposals on CSR are also one of the main types of proposals at firms’ annual shareholder meetings. However, even though the frequency of CSR proposals at annual meetings is comparable to other types of shareholder proposals, the approval rate of CSR proposals is significantly lower than that of other types of proposals, meaning that most CSR proposals are not recommended by the annual meeting to the board of directors for further approval. Motivated by this stylized fact, this study investigates the value of the submission of CSR shareholder proposals. Using a regression discontinuity design with shareholder proposal data of US public companies between 2006 and 2019, this study examines the importance of shareholders’ interest in CSR for firm valuation. Interestingly, while the CSR proposals themselves are typically not approved, the submission of CSR proposals by shareholders at annual meetings matters for the value impact of other types of shareholder proposals. More specifically, the causal effect of approving a corporate governance proposal on shareholder value is significantly positive only if the corporate governance proposal is voted together with a CSR proposal at the same meeting, i.e., the presence of CSR proposals is important for firm value through its interrelations with corporate governance proposals. This shows that the submission of CSR shareholder proposals has significant value implications, even if the CSR proposals themselves are not approved at annual meetings.